SISTEM INFORMASI PENDATAAN TENAGA KERJA INDONESIA BERBASIS WEB PADA PT. LAATANSA LINTAS INTERNASIONAL: SISTEM INFORMASI PENDATAAN TENAGA KERJA INDONESIA BERBASIS WEB PADA PT. LAATANSA LINTAS INTERNASIONAL - Linda Norhan; Tedi Kustandi (Institute of Computer Science (IOCS), 2019)
PT. Laatansa Lintas Internasional is a service distributor company engaged in employment. This company distributes Indonesian Workers to several countries such as Malaysia, Singapore, Hong Kong and Taiwan. The system that runs on PT.Laatansa Lintas Internasional is still using manual methods, one of the data processing processes of Indonesian labor that is running is by collecting all the data into Microsoft Excel. Therefore there needs to be a new innovation in the process of processing Indonesian labor data, namely by designing computerized application systems to facilitate processing of data at PT Laatansa Lintas Internasional and minimizing errors in inputting data. Indonesian labor data collection system that is better than the system that has been running before. Designing Information System for Indonesian Manpower Data Collection at PT. The International Cross Laatansa to be made includes: Draft Forms of Indonesian labor data, flying data and value data, narrative procedures and flowcharts, context diagrams, data flow diagrams (DFD), entity relationship diagrams (ERD), tables used Database Design , Design of Input and Output Display which is implemented using PHP programming language and MySql software as data storage media. This data collection provides information on Indonesian labor data reports, reports on Indonesian labor exam data and flight data reports on Indonesian workers. From the explanation above, it can be concluded that the system running in PT. Laatansa Lintas Internasional is still less effective in data collection of Indonesian Manpower data so that the author will make an application that can record data on Indonesian Workers on a computer to facilitate recording and reporting from the application itself.